ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2021 DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING - Fitrianingsih, Desiana; Hamdun, Edy Kusnadi; Wiryaningtyas, Dwi Perwitasari (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Investors assess the performance of a company through its Stock price. The number of requests and offers for shares that occur in the capital market affects the high and low prices of company shares. If the company's performance is in good condition, then the company's shares will be in demand by investors so that the share price will be high. The purpose of this study was to analyze and examine the factors that influenced stock prices in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange with Dividend policy as an intervening variable. The sampling technique in this study was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural-Partial Least Square Equation Model (PLS-SEM). The results of the direct influence hypothesis test show the following results. Debt to Equity Ratio has a positive but not significant effect on Dividend policy. Net Profit Margin has a negative but not significant effect on Dividend policy. Debt to Equity Ratio has a negative but not significant effect on Stock prices. Net Profit Margin has a significant negative effect on Stock prices. Dividend policy has a significant positive effect on Stock prices. The results of the indirect effect hypothesis test show that the Debt to Equity Ratio variable has a positive but not significant effect on Stock prices through Dividend policy. Net Profit Margin has a negative but not significant effect on Stock prices through Dividend policy.